Consolidation characteristics of high-water-content slurries improved by flocculation-enhanced surcharge (vacuum) preloading method - Han, Chao; Fan, Zhou; Zhang, Rongjun; Cheng, Jinkang; Sun, Ke; Peng, Qian (Frontiers in Materials, 2023)
The high volume and unfavorable properties of high-water-content slurries make their treatment difficult and costly. Improving the slurries through prefabricated drains combined with surcharge or vacuum preloading represents an environmental and economic means of reusing these slurries as subsoil. As conventional methods are inefficient in dealing with low-permeability slurries, flocculation is often applied. In this study, the influence of the flocculant dosage on the drainage behavior is observed, and the secondary consolidation of the slurries is examined through laboratory tests. Flocculation is found to accelerate the consolidation process, although the flocculant dosage has an optimal value when combined with the surcharge preloading method. The coefficient of secondary consolidation is more significant in slurries improved by the flocculation-enhanced surcharge (vacuum) preloading method. The use of flocculation must be carefully controlled.